The influence of citizen interaction with the police on crime-reporting behavior: its manifestations among university students - Avdija, Avdi S (2010)
"Citizen's crime-reporting is generally low, with a number of factors affecting its prevalence and incidence. Research suggests that there is an interrelationship between the type of contacts citizens have with the police (e.g., citizen-initiated or police-initiated), attitudes toward the police, police behavior, and crime-reporting behavior. To determine whether citizen interactions with the police infl uence crime-reporting behavior and attitudes toward the police, this study tested four research hypotheses. The fi ndings of this study suggest that predictors such as citizen-initiated contacts, police-initiated contacts, frequency of those contacts, and exposure to media about police misconduct cannot be used as a group but rather individually to predict all three different levels of crimereporting behavior (i.e., reporting of less serious crimes, reporting of medium-level crimes, and reporting of serious crimes)." (author's abstract)